2016
DOI: 10.4103/0976-237x.183068
|View full text |Cite
|
Sign up to set email alerts
|

Application of transtheoretical model to assess the compliance of chronic periodontitis patients to periodontal therapy

Abstract: Background:The present cross-sectional survey study was conducted to assess whether the transtheoretical model for oral hygiene behavior was interrelated in theoretically consistent directions in chronic periodontitis patients and its applicability to assess the compliance of the chronic periodontitis patients to the treatment suggested.Materials and Methods:A total of 150 chronic periodontitis patients were selected for the proposed study. The selected patients were given four questionnaires that were constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Thereby, patients did not only show reduced DCB, the average score of perceived benefits and self‐efficacy was lower in them, too. Emani et al ( 2016 ) showed that the perceived self‐efficacy score and perceived benefits are higher in the final stages of the behavior. According to the transtheoretical theory, self‐efficacy and perceived benefits as well as social support are higher in the final stages of behavior (Sardi et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, patients did not only show reduced DCB, the average score of perceived benefits and self‐efficacy was lower in them, too. Emani et al ( 2016 ) showed that the perceived self‐efficacy score and perceived benefits are higher in the final stages of the behavior. According to the transtheoretical theory, self‐efficacy and perceived benefits as well as social support are higher in the final stages of behavior (Sardi et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, cons and self-efficacy were common factors of stage advance in all behaviors, and the pros were specific to the reduction of saturated fats. Self-efficacy has been shown to play an important role as a predictor of higher stages of healthy behaviors [ 12 , 25 , 26 , 27 ], and pros and cons have been associated with a reduction of fat in the diet [ 25 ], but the results for exercise are mixed [ 26 , 28 , 29 ]. Notably, susceptibility or severity of complications did not make a difference in stage of readiness, contrary to what the Health Belief Model proposed [ 6 ].…”
Section: Discussionmentioning
confidence: 99%